Analysis of Quran Education Problems in Majority Muslim Countries - Engkizar, Engkizar; Jaafar, Azhar; Sarianto, Debi; Ayad, Nahid; Rahman, Achyar; Febriani, Afifah; Oktavia, Gifa; Guspita, Rosi; Rahman, Ikhwan (International Journal of Islamic Studies Higher Education, 2024)
Quranic education is a crucial aspect of shaping the identity and values of Muslim societies. However, Muslim-majority countries face various challenges in providing high-quality Quranic education. This study aims to analyze the problems related to Quranic education in these countries. The research employed a qualitative method with a case study approach in several majority-Muslim countries. Data were collected through interviews with Quranic education experts, teachers, and students, as well as through document and literature analysis. All data were analyzed using Miles and Huberman's interactive analysis technique with NVivo 12 software. The research findings indicate that the challenges in Quranic education include the absence of legislation governing the Quranic teaching profession, limited availability of qualified teachers, low competence in instructional management, the fact that not all Quran teachers possess a bachelor's degree in Quranic education, insufficient professional development due to a lack of continuous training, the profession's lack of appeal to Islamic scholars because it does not promise a future career, and inadequate teacher compensation. The findings underscore the importance of implementing systematic and strategic improvements to enhance the quality of Quranic education.